Determinación de Staphylococcus aureus y Aerobios mesófilos en carne de cerdo hornado expendida en mercado de Azogues - Cuenca Cajas, Irina Geovanna (2023)
In southern Ecuador, baked pork is a highly demanded traditional dish, its preparation and sale is often carried out in unsuitable hygienic - sanitary conditions, which can trigger food health problems, so the objective of this study was to determine the presence of Staphylococcus aureus and mesophilic aerobes and the factors associated with their presence in baked pork sold in Azogues markets. The research design was cross-sectional observational, in which 270 samples of baked pork were collected from 30 retail outlets. Through microbiological cultures, the presence of Staphylococcus aureus was found in 16.67% of the places of sale of the product and a count of mesophilic aerobes that exceeds the maximum required in the NTE INEN 1529-5 regulation in 97.30% of places of sale. Therefore, baked pork from the Azogues markets present a considerable amount of microorganisms which could be a risk to public health. It is advisable to carry out more studies to clarify serotypes and possible factors that have a greater influence on food contamination.